PET Imaging of brain muscarinic receptors with 18F-Fluorobenzyl-Dexetimide: A first in human study. (30th October 2021) - Rowe, Christopher C.; Krishnadas, Natasha; Ackermann, Uwe; Doré, Vincent; Goh, Rachel Y.W.; Guzman, Rodney; Chong, Lee; Bozinovski, Svetlana; Mulligan, Rachel; Kanaan, Richard; Dean, Brian; Villemagne, Victor L.
Highlights: This is the first-in-human use of FDEX PET. FDEX is the first fluorine-18 (F-18) labelled PET tracer for muscarinic receptors. This allows it to be produced more efficiently and distributed more widely than existing carbon-11 labelled tracers that require an on-site cyclotron. FDEX provides high quality images of brain mACh receptors. FDEX has low variance in the level of binding to mACh receptors across normal young adults suggesting it may be sensitive for detection of changes in receptor density or binding in disease states. Imaging time and measurement of tissue ratios using the cerebellum as the reference region are suitable for application to patients with schizophrenia or dementia. Abstract: M1 and M4 muscarinic receptor (mAChR) agonists are under development for the treatment of schizophrenia, Alzheimer's and Parkinson's disease. We performed first-in-human PET imaging of mAChR with 18 F-Fluorobenzyl-Dexetimide (FDEX) in 10 healthy participants (29.4±4.3yrs). Four underwent dynamic brain scanning for 240 min, and then six underwent static brain scans at 120 and 160-min post injection of 250 MBq of FDEX. Gjedde-Patlak graphical analysis was applied to determine the influx constant (Ki). Regional tissue ratios (SUVR) were calculated using the cerebellar cortex as the reference region. No adverse events were observed. The tracer showed good brain entry (∼4.2% ID at 5 min) but irreversible distribution kinetics over four hours in regions of high mAChR. Binding was consistent with the distribution of mAChR receptors with striatum > cortex > hippocampus >> thalamus >>> cerebellum with low variance in regional binding between subjects. Ki was 0.42±0.04 in the putamen, 0.27±0.01 in frontal cortex, 0.25±0.02 in the hippocampus and 0.10±0.01 in the thalamus. SUVR at 120 and 240 min. were highly correlated with these Ki values with R 2 of 0.91 and 0.99 respectively. FDEX yields high quality brain images with uptake in the known distribution of mAChR with remarkably little variance between normal subjects.